Assessing the integration of social marketing principles in ivory demand management interventions in China and Southeast Asia - Molly R. C. Brown; Victoria K. Wells; Colin M. Beale (Conservation Biology, 2026)
Consumer demand for ivory perpetuates the unsustainable and illegal killing of African elephants and other wildlife species. Interventions that aim to change consumer behavior are increasingly recognized as a crucial element of demand management. However, poor design and implementation have limited their effectiveness. We evaluated how ivory demand‐management interventions in China and neighboring Southeast Asian countries align with best practices from the behavioral field of social marketing. Through a literature review, we identified 55 interventions conducted from 2008 to 2022. We used 2 social marketing frameworks to assess each intervention's capacity to influence behavior. We conducted semistructured interviews with 5 intervention practitioners to provide contextual grounding for our review findings. From 2018 to 2022, social marketing principles were more frequently applied and interventions were of a higher quality ( n = 26) than interventions conducted from 2008 to 2017, reflecting a growing adoption of consumer‐insight‐driven strategies. Since 2018, 7 interventions applied no social marketing principles, and 9 interventions, to varying degrees, included monitoring and evaluation. Although 13 interventions contained some theoretical considerations, these were often vague and superficial. Despite identifying a shift from experiential practices to evidence‐based approaches over time, the shift was largely restricted to communications‐based social and behavior change approaches. This left the wide range of social marketing approaches underused. Ivory demand management must improve the breadth and depth of social marketing used to contribute to long‐term elephant conservation. We suggest all consumer approaches tackling demand for wildlife meaningfully consider integrating behavioral theories in intervention design, undertake primary or secondary research to enable evidence‐led decision‐making, conduct systematic monitoring for evidence‐based learning and adaptation, and use impact and process evaluation methods to understand the mechanisms and magnitude of behavioral change following interventions.

Estimating area of occupancy for specialist oil-collecting bees: Integrating species distribution models and spatial overlays to assess extinction risk - Annalie Melin; Jonathan F. Colville; John C. Manning; Colin M. Beale (Journal of Insect Conservation, 2026)

Species Contributions to Biotic Homogenisation and Differentiation - Jack H. Hatfield; Jonathan D. Gordon; Colin M. Beale; Chris D. Thomas (Global Ecology and Biogeography, 2026)
Aim Homogenisation (decreasing beta‐diversity) among biological assemblages is often interpreted as being caused by already‐widespread species increasing. The link between individual species level trends and homogenisation between assemblages, however, has not been fully addressed, with most studies focused solely on either assemblage level or species level changes. Here we aim to test the widely held hypothesis that homogenisation is driven by the decrease of localised species and increase of those already widespread using species contribution to beta‐diversity. Location North America, Europe, South Africa. Time Period 1970 to 2019, 1966 to 1996, 11,700 years ago to present, 2011 to 2021, 1960 to 2016. Major Taxa Studied Birds, plants, benthos and mammals. Methods Here, we consider individual species contributions to spatial beta‐diversity and how these change over time. We focus on the relative contributions of localised and widespread species across five case studies to determine which are contributing most to homogenisation. Results Species occurring in around half of sites provided the greatest contributions to beta‐diversity at a given time, but not through time. The most widespread species (> 0.75 of sites) contributed little to beta‐diversity change, with this most apparent in highly nested assemblages. In contrast, localised species (initially in Main Conclusions This challenges the hypothesis that widespread generalist species are the main drivers of homogenisation, underlining the importance of rare species and of nestedness to patterns of beta‐diversity change. Conservation interventions to increase localised species occurrence would do more to limit homogenisation than attempts to control already‐widespread species or prevent others becoming widespread, especially when assemblages are highly nested.

Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Assessing inconsistencies in historical land-use reconstructions for Africa at 1800 - Tabitha K. Kabora; Daryl Stump; Chris D. Thomas; Colin M. Beale (Regional Environmental Change, 2024)
Reconstructing historical land-use and land-cover change (LULCC) inevitably involves interpolation across regions for which there is limited data to support reconstructions. Here, we evaluate the extent to which the global land-use model HYDE v3.2.1 reflects historical land use in sub-Saharan Africa (including Madagascar) when compared to archaeological and historical reconstructions. Both the HYDE models and Widgren’s archaeological and historical reconstructions estimate that agriculture was widely scattered across sub-Saharan Africa in 1800 CE. However, in steep terrain, at slopes greater than 10°, the HYDE model estimated 0% cropland allocation while archaeological and historical observations suggest intensive, mixed and extensive farming was common in these areas. In addition, while HYDE allocates farmland primarily into high-quality soils, archaeological reconstructions suggest that intensive farming occurred across a wide range of soil qualities. Gaps in our knowledge of cropland distribution have significant impacts on models of biodiversity change since understanding biodiversity in the Anthropocene is reliant on our understanding of past land-use changes. While HYDE’s mismatches are known, the research presented here provides an important resource in identifying where these allocation rules fail. These mismatches in global land-use models such as HYDE might also be replicated for other regions of the world, such as South America. These mismatches also need to be accounted for when generating model projections that use historical land-use models to impute present and future trends in land-use, climate and biodiversity change. Localised archaeological and historical data can therefore be used to support historical global land-use reconstructions for Africa and other regions across the world.

Spatio‐temporal integrated Bayesian species distribution models reveal lack of broad relationships between traits and range shifts - Joris H. Wiethase; Philip S. Mostert; Christopher R. Cooney; Robert B. O'Hara; Colin M. Beale (Global Ecology and Biogeography, 2024)
Aim Climate change and habitat loss or degradation are some of the greatest threats that species face today, often resulting in range shifts. Species traits have been discussed as important predictors of range shifts, with the identification of general trends being of great interest to conservation efforts. However, studies reviewing relationships between traits and range shifts have questioned the existence of such generalized trends, due to mixed results and weak correlations, as well as analytical shortcomings. The aim of this study was to test this relationship empirically, using analytical approaches that account for common sources of bias when assessing range trends. Location Tanzania, East Africa. Time period 1980–1999 and 2000–2020. Major taxa studied 57 savannah specialist birds found in Tanzania, belonging to 26 families and 11 orders. Methods We applied recently developed integrated spatio‐temporal species distribution models in R‐INLA, combining citizen science and bird Atlas data to estimate ranges of species, quantify range shifts, and test the predictive power of traditional trait groups, as well as exposure‐related and sensitivity traits. We based our study on 40 years of bird observations in East African savannahs, a biome that has experienced increasing climatic and non‐climatic pressures over recent decades. We correlated patterns of change with species traits using linear regression models. Results We find indications of relationships identified by previous research, but low average explanatory power of traits from an ecological perspective, confirming the lack of meaningful general associations. However, our analysis finds compelling species‐specific results. Main conclusions We highlight the importance of individual assessments while demonstrating the usefulness of our analytical approach for analyses of range shifts.

Human modification of land cover alters net primary productivity, species richness and their relationship - Shuyu Deng; Colin M. Beale; Philip J. Platts; Chris D. Thomas (Global Ecology and Biogeography, 2024)
Aim Humans have altered ecosystem productivity and biodiversity worldwide by changing land‐cover types and management. High local species richness is commonly found in geographic areas and ecosystems with high net primary productivity (NPP), but the long‐term effects of modification on productivity and biodiversity change, and particularly on the relationship between the two, are poorly understood. Here we evaluate whether human modification tends to increase biodiversity in low‐productivity ecosystems (where human management is likely to increase productivity) and decrease biodiversity in ecosystems that were originally high‐productive. Location Global. Time Period 2001–2013. Major Taxa Studied Plants, mammals, birds, hexapods, arachnids, other terrestrial invertebrates, amphibians, reptiles and fungi. Methods We assembled a large worldwide dataset of NPP and associated species richness from MODIS land cover and NPP products and the PREDICTS biodiversity database, involving 11,849 sites. This enabled comparisons of species richness and NPP differences between samples of relatively natural and human‐modified vegetation within the same geographic regions, considering 102 types of land‐cover transitions. Results (1) Modification from non‐forest vegetation to forests on average increased NPP by 7.76%, and vice versa. (2) Human modification of less productive areas tended to increase NPP and vice versa, with stronger effects of major modification. (3) However, site‐level species richness decreases were associated with nearly all land‐cover transitions from relatively natural to modified vegetation. (4) Despite expectations, we found no significant relationship between species richness differences (between relatively natural and modified vegetation) and productivity differences, when considering conversions across land‐cover types and excluding human‐appropriated productivity in croplands. Main Conclusions Human modification tends to increase NPP in low‐productivity ecosystems, but species richness declines are associated with most major human‐induced land‐cover changes. Therefore, increasing or decreasing NPP did not generate corresponding increases or decreases in species richness, contrary to expectations of the general species richness‐productivity relationship.

Revising vulnerability assessments of montane birds in the colombian páramo to account for threats from climate change - Christopher J Wheatley; Colin M Beale; Piran C L White; Adrián Villaseñor; Adriana Sanchez; Charles A Cunningham; Jane K Hill (Biodiversity and Conservation, 2023)
Tropical montane ecosystems are highly vulnerable to global climate change, but their species-level conservation vulnerability assessments generally do not incorporate climate threats. The Colombian páramo is a highly diverse montane ecosystem but it contains relatively few species currently identified as threatened on the IUCN Red List. We explore whether current assessments need revising to account for climate change threats for páramo species. We use a climate change vulnerability assessment framework to evaluate the risks and opportunities from climate change for 60 bird species within the Colombian páramo. We explore two potential climate change scenarios (RCP 2.6 and RCP 8.5), representing best and worst-case projections. We find that more than half (52–68%, depending on the scenario) of bird species will be threatened by climate change by the end of the century, but a very poor agreement between the current conservation status of species and their climate vulnerability score. We find ~ 90% of species identified as climate-threatened are not currently identified as being of conservation concern, representing a substantial new suite of priority species within the Colombian páramo. Overall, we identify up to 34 páramo bird species that are threatened by climate change but not currently listed as being of conservation concern. Similar mismatches may also occur in other montane taxa and so updating species risk assessments to account for climate change is urgently needed. Implementation of appropriate conservation actions is also needed to reduce species’ risks from climate change.

Identifying priority locations to protect a wide-ranging endangered species - Natasha M. Peters; Corinne J. Kendall; Jacob G. Davies; Claire Bracebridge; Aaron Nicholas; Msafiri P. Mgumba; Colin M. Beale (Biological Conservation, 2023)

Combining models for animal tracking: Defining behavioural states to understand space use for conservation - Natasha M. Peters; Colin M. Beale; Claire Bracebridge; Msafiri P. Mgumba; Corinne J. Kendall (Journal of Biogeography, 2022)
Aim Rapid advances in technology have created tools able to explore how animals differ in their use of the environment based on behaviour, which can provide insights into the ecology of endangered animals and the threats they face. Though threatened, we know little of vultures' spatial ecology. We examine the external variables that affect vultures' decisions regarding space use, specifically during foraging and feeding when they are at greatest risk for encountering threats, and use this to inform effective conservation interventions. Location Tanzania, specifically Southern Tanzanian protected area networks. Taxon Gyps africanus. Methods We tracked 26 African white‐backed vultures between 2015 and 2019 in Southern Tanzania. Using hidden Markov models to identify behaviour from raw GPS points and point process models to spatially analyse these behaviours, we tested resource selection decisions in vultures during foraging and feeding, when they are at greatest risk of poisoning. Results African white‐backed vultures are most likely to forage early in the day outside National Parks, specifically in Game Reserves and Wildlife Management Areas, but avoid areas with high livestock numbers to feed. Eastern and Western populations showed slight differences in preferences, highlighting the need for population level considerations. When not selecting for behaviour, closeness to rivers and habitat openness were more important than protected area status for predicting vulture use. Main conclusions Through combining complex analyses, we identified results which simple statistical analyses could not offer. Hidden Markov models and point process models are complementary and can be used to define specific behaviours and associated resource selection. These results provide insight into how animals use their habitat explicitly rather than describing where they spend most of their time. This adds to the growing evidence that although National Parks are important, the management of surrounding areas must be included in conservation efforts.

Multi-taxa spatial conservation planning reveals similar priorities between taxa and improved protected area representation with climate change - Rob Critchlow; Charles A. Cunningham; Humphrey Q. P. Crick; Nicholas A. Macgregor; Michael D. Morecroft; James W. Pearce-Higgins; Tom H. Oliver; Matthew J. Carroll; Colin M. Beale (Biodiversity and Conservation, 2022)
Protected area (PA) networks have in the past been constructed to include all major habitats, but have often been developed through consideration of only a few indicator taxa or across restricted areas, and rarely account for global climate change. Systematic conservation planning (SCP) aims to improve the efficiency of biodiversity conservation, particularly when addressing internationally agreed protection targets. We apply SCP in Great Britain (GB) using the widest taxonomic coverage to date (4,447 species), compare spatial prioritisation results across 18 taxa and use projected future (2080) distributions to assess the potential impact of climate change on PA network effectiveness. Priority conservation areas were similar among multiple taxa, despite considerable differences in spatial species richness patterns; thus systematic prioritisations based on indicator taxa for which data are widely available are still useful for conservation planning. We found that increasing the number of protected hectads by 2% (to reach the 2020 17% Aichi target) could have a disproportionate positive effect on species protected, with an increase of up to 17% for some taxa. The PA network in GB currently under-represents priority species but, if the potential future distributions under climate change are realised, the proportion of species distributions protected by the current PA network may increase, because many PAs are in northern and higher altitude areas. Optimal locations for new PAs are particularly concentrated in southern and upland areas of GB. This application of SCP shows how a small addition to an existing PA network could have disproportionate benefits for species conservation.

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Detecting deterrence from patrol data - Andrew D. M. Dobson; E. J. Milner‐Gulland; Colin M. Beale; Harriet Ibbett; Aidan Keane (Conservation Biology, 2019)
The threat posed to protected areas by the illegal killing of wildlife is countered principally by ranger patrols that aim to detect and deter potential offenders. Deterring poaching is a fundamental conservation objective, but its achievement is difficult to identify, especially when the prime source of information comes in the form of the patrols’ own records, which inevitably contain biases. The most common metric of deterrence is a plot of illegal activities detected per unit of patrol effort (CPUE) against patrol effort (CPUE‐E). We devised a simple, mechanistic model of law breaking and law enforcement in which we simulated deterrence alongside exogenous changes in the frequency of offences under different temporal patterns of enforcement effort. The CPUE‐E plots were not reliable indicators of deterrence. However, plots of change in CPUE over change in effort (ΔCPUE‐ΔE) reliably identified deterrence, regardless of the temporal distribution of effort or any exogenous change in illegal activity levels as long as the time lag between patrol effort and subsequent behavioral change among offenders was approximately known. The ΔCPUE‐ΔE plots offered a robust, simple metric for monitoring patrol effectiveness; were no more conceptually complicated than the basic CPUE‐E plots; and required no specialist knowledge or software to produce. Our findings demonstrate the need to account for temporal autocorrelation in patrol data and to consider appropriate (and poaching‐activity‐specific) intervals for aggregation. They also reveal important gaps in understanding of deterrence in this context, especially the mechanisms by which it occurs. In practical applications, we recommend the use of ΔCPUE‐ΔE plots in preference to other basic metrics and advise that deterrence should be suspected only if there is a clear negative slope. Distinct types of illegal activity should not be grouped together for analysis, especially if the signs of their occurrence have different persistence times in the environment.

Pyrodiversity interacts with rainfall to increase bird and mammal richness in African savannas - Colin M. Beale; Colin J. Courtney Mustaphi; Thomas A. Morrison; Sally Archibald; T. Michael Anderson; Andrew P. Dobson; Jason E. Donaldson; Gareth P. Hempson; James Probert; Catherine L. Parr (Ecology Letters, 2018)
Fire is a fundamental process in savannas and is widely used for management. Pyrodiversity, variation in local fire characteristics, has been proposed as a driver of biodiversity although empirical evidence is equivocal. Using a new measure of pyrodiversity (Hempson et al .), we undertook the first continent‐wide assessment of how pyrodiversity affects biodiversity in protected areas across African savannas. The influence of pyrodiversity on bird and mammal species richness varied with rainfall: strongest support for a positive effect occurred in wet savannas (> 650 mm/year), where species richness increased by 27% for mammals and 40% for birds in the most pyrodiverse regions. Range‐restricted birds were most increased by pyrodiversity, suggesting the diversity of fire regimes increases the availability of rare niches. Our findings are significant because they explain the conflicting results found in previous studies of savannas. We argue that managing savanna landscapes to increase pyrodiversity is especially important in wet savannas.

Climate change vulnerability for species—Assessing the assessments - Christopher J. Wheatley; Colin M. Beale; Richard B. Bradbury; James W. Pearce‐Higgins; Rob Critchlow; Chris D. Thomas (Global Change Biology, 2017)
Climate change vulnerability assessments are commonly used to identify species at risk from global climate change, but the wide range of methodologies available makes it difficult for end users, such as conservation practitioners or policymakers, to decide which method to use as a basis for decision‐making. In this study, we evaluate whether different assessments consistently assign species to the same risk categories and whether any of the existing methodologies perform well at identifying climate‐threatened species. We compare the outputs of 12 climate change vulnerability assessment methodologies, using both real and simulated species, and validate the methods using historic data for British birds and butterflies (i.e. using historical data to assign risks and more recent data for validation). Our results show that the different vulnerability assessment methods are not consistent with one another; different risk categories are assigned for both the real and simulated sets of species. Validation of the different vulnerability assessments suggests that methods incorporating historic trend data into the assessment perform best at predicting distribution trends in subsequent time periods. This study demonstrates that climate change vulnerability assessments should not be used interchangeably due to the poor overall agreement between methods when considering the same species. The results of our validation provide more support for the use of trend‐based rather than purely trait‐based approaches, although further validation will be required as data become available.

Protected area networks and savannah bird biodiversity in the face of climate change and land degradation - Colin M. Beale; Neil E. Baker; Mark J. Brewer; Jack J. Lennon (Ecology Letters, 2013)
The extent to which climate change might diminish the efficacy of protected areas is one of the most pressing conservation questions. Many projections suggest that climate‐driven species distribution shifts will leave protected areas impoverished and species inadequately protected while other evidence suggests that intact ecosystems within protected areas will be resilient to change. Here, we tackle this problem empirically. We show how recent changes in distribution of 139 Tanzanian savannah bird species are linked to climate change, protected area status and land degradation. We provide the first evidence of climate‐driven range shifts for an African bird community. Our results suggest that the continued maintenance of existing protected areas is an appropriate conservation response to the challenge of climate and environmental change.

The impact of increased food availability on survival of a long‐distance migratory bird - Adam M. Seward; Colin M. Beale; Lucy Gilbert; T. Hefin Jones; Robert J. Thomas (Ecology, 2013)
Temperature‐, rainfall‐ and habitat‐driven change in food availability is one likely mechanism by which anthropogenic factors may affect animal population dynamics and species distributions. Long‐distance migratory birds must synchronize their migrations with food availability at locations hundreds or thousands of kilometers apart, so changes in the overall abundance of food or the phenology of peaks in food availability may be critical factors influencing annual survival. In this study we used experimental food supplementation at a breeding site to examine and compare the impact of changing food supply on annual survival of adult migratory birds and their offspring. We provided supplemental food to Northern Wheatears ( Oenanthe oenanthe ) breeding on Fair Isle, UK, to infer the sensitivity of annual survival to increases in natural food availability. Food‐supplemented wheatears exhibited higher rates of annual survival than control wheatears, and the strength of this effect varied with age. Food supplementation led to 1.56 times higher annual survival of juveniles and 1.22 times higher survival of adults. Survival of juveniles was related to their own food availability as fledglings, but not to whether their parents were food‐supplemented or unfed control adults. This increased survival, combined with increased breeding productivity associated with food supplementation, implies that an increase in natural food availability, of the magnitude simulated in our experiment, would increase the population growth rate of wheatears on Fair Isle from approximately λ = 0.93 (a contracting population) to λ = 1.14 (an expanding population).

Palatability mapping: a koala's eye view of spatial variation in habitat quality - Ben D. Moore; Ivan R. Lawler; Ian R. Wallis; Colin M. Beale; William J. Foley (Ecology, 2010)
Ecologists trying to understand the value of habitat to animals must first describe the value of resources contained in the habitat to animals and, second, they must describe spatial variation in resource quality at a resolution relevant to individual animal foraging. We addressed these issues in a study of koalas ( Phascolarctos cinereus ) in a Eucalyptus woodland. We measured beneficial and deterrent chemical characteristics as well as the palatability of trees using a near‐infrared spectroscopic model based on direct feeding experiments. Tree use by koalas was influenced by tree size and foliar quality but was also context‐dependent: trees were more likely to be visited if they were surrounded by small, unpalatable trees or by large, palatable trees. Spatial autocorrelation analysis and several mapping approaches demonstrated that foliar quality is spatially structured in the woodland at a scale relevant to foraging decisions by koalas and that the spatial structure is an important component of habitat quality.

Revealing ecological networks using Bayesian network inference algorithms - Isobel Milns; Colin M. Beale; V. Anne Smith (Ecology, 2010)
Understanding functional relationships within ecological networks can help reveal keys to ecosystem stability or fragility. Revealing these relationships is complicated by the difficulties of isolating variables or performing experimental manipulations within a natural ecosystem, and thus inferences are often made by matching models to observational data. Such models, however, require assumptions—or detailed measurements—of parameters such as birth and death rate, encounter frequency, territorial exclusion, and predation success. Here, we evaluate the use of a Bayesian network inference algorithm, which can reveal ecological networks based upon species and habitat abundance alone. We test the algorithm's performance and applicability on observational data of avian communities and habitat in the Peak District National Park, United Kingdom. The resulting networks correctly reveal known relationships among habitat types and known interspecific relationships. In addition, the networks produced novel insights into ecosystem structure and identified key species with high connectivity. Thus, Bayesian networks show potential for becoming a valuable tool in ecosystem analysis.

Regression analysis of spatial data - Colin M. Beale; Jack J. Lennon; Jon M. Yearsley; Mark J. Brewer; David A. Elston (Ecology Letters, 2010)
Ecology Letters (2010) 13: 246–264 Abstract Many of the most interesting questions ecologists ask lead to analyses of spatial data. Yet, perhaps confused by the large number of statistical models and fitting methods available, many ecologists seem to believe this is best left to specialists. Here, we describe the issues that need consideration when analysing spatial data and illustrate these using simulation studies. Our comparative analysis involves using methods including generalized least squares, spatial filters, wavelet revised models, conditional autoregressive models and generalized additive mixed models to estimate regression coefficients from synthetic but realistic data sets, including some which violate standard regression assumptions. We assess the performance of each method using two measures and using statistical error rates for model selection. Methods that performed well included generalized least squares family of models and a Bayesian implementation of the conditional auto‐regressive model. Ordinary least squares also performed adequately in the absence of model selection, but had poorly controlled Type I error rates and so did not show the improvements in performance under model selection when using the above methods. Removing large‐scale spatial trends in the response led to poor performance. These are empirical results; hence extrapolation of these findings to other situations should be performed cautiously. Nevertheless, our simulation‐based approach provides much stronger evidence for comparative analysis than assessments based on single or small numbers of data sets, and should be considered a necessary foundation for statements of this type in future.

Modeling the Effects of Limiting the Number of Visitors on Failure Rates of Seabird Nests - COLIN M. BEALE; P. MONAGHAN (Conservation Biology, 2005)
Most attempts to manage disturbance by visitors to nature reserves concentrate on limiting visitor access in some way, which is often unpopular with both visitors and managers. In a few nature reserves the daily numbers of visitors are limited, an action that need not necessarily reduce the total number of visitors. As a test of the assumptions that underlie this management practice, we examined the relationship between daily visitor numbers and daily failure rates of nests in two species of seabirds. Daily failure rates for Black‐legged Kittiwakes (Rissa tridactyla) were weakly correlated with daily visitor numbers but indicated that capping daily visitor numbers slightly reduced overall breeding success. This was not the case for Common Murres (Uria aalge), where failure rate declined seasonally but was not significantly correlated with visitor numbers. For some species, it appears that capping daily visitor numbers may have small conservation costs.